2016
DOI: 10.24191/jeeir.v4i2.9082
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Return of Shariah with Underlying Indices of National Stock Exchange of India: A Case of 3SLS and GMM Estimation

Abstract: Shariah indices can be used to construct socially reliable investment products that are attractive for those, who do not wish to invest in undesired business. National Stock Exchange of India introduced Nifty 50 Shariah and Nifty 500 Shariah indices to provide alternative i The study is an attempt to reveal the relationship between Nifty 50 Shariah and Nifty 500 Shariah with their underlying indices, Nifty 50 and Nifty 500.For this purpose a period of 01/01/2007 to 31/12/2015 is taken. Based on various objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…However, this paper differs from the above in the frequency of analysis. Siddiqui and Sheikh (2016) report lower volatility of the SCEIs, for the period 2007-2015, on the same indices, but the authors do not verify for statistical significance. However, risks of both passive and active SCEIs significantly differ from their non-Sharīʿah counterparts during periods of low market volatility, in the shorter investment horizons.…”
Section: Correlation Of Returnsmentioning
confidence: 83%
See 4 more Smart Citations
“…However, this paper differs from the above in the frequency of analysis. Siddiqui and Sheikh (2016) report lower volatility of the SCEIs, for the period 2007-2015, on the same indices, but the authors do not verify for statistical significance. However, risks of both passive and active SCEIs significantly differ from their non-Sharīʿah counterparts during periods of low market volatility, in the shorter investment horizons.…”
Section: Correlation Of Returnsmentioning
confidence: 83%
“…Due to the absence of the sizable number of Islamic or Sharīʿah-compliant mutual funds offered in India, Indian studies considered Sharīʿah Indices as proxies of SCEIs. While Munusamy and Natarajan (2011) during the period 2007-2010, did not find any significant difference between the returns of the Nifty Sharīʿah 50 Index and Nifty 50 Index; Siddiqui and Sheikh (2016) found that Sharīʿah Indices yield relatively better returns. Habib and Islam (2014) have shown that S&P BSE 500 Sharīʿah underperforms S&P BSE 500.…”
Section: Review Of Relevant Literaturementioning
confidence: 88%
See 3 more Smart Citations